Refleksi tentang Kebenaran Ilmu - Wahyudi, Imam (Jurnal Filsafat "WISDOM", 2007)
Studies on the truth of knowledge has often been conducted, especially one that focuses on the criteria of truth. So far, these studies is still and remains sectoral in its characters since scientist pay too much attention to prove the strength of their own scientific group. Researcher seeks to achieve the whole picture of truth, from metaphisical to epistemological ones. The conceptions of truthas an answer to the probelms of science can be drawn into various ways: the purpose of science, the meaning of truth, the types of truth, the criteria of truth and the character to truth. These various answers is a part of the nature of philosophical investigations itself which is subjective and depend so much on the philosopher's point of views.In its methodical sense, science represents a combinations of Rationalism and Empiricism and thus the scientific truth must be coherent with truth of in scientific system as well as with the fact. There is no a single standar in measuring the truth of science as there are various objects, method, and paradigm of science. The nature of scientific truth is probable, tentative, evolutionary, and even relative and thus it would reach perfection.